Investigating the role of Akkermansia muciniphila Akk11 in modulating obesity and intestinal dysbiosis: a comparative study of live and pasteurized treatments - Feng, Songhui; Wang, Weitao; Zhang, Xin; Helal, Shimaa Elsayed; Peng, Nan; Zhang, Zhenting (Frontiers in Microbiology, 2025)
IntroductionObesity has become a major global health concern and is closely associated with imbalances in gut microbiota and chronic low-grade inflammation. Probiotics have been explored for their potential to prevent or alleviate obesity, especially in the case of Akkermansia muciniphila. While the standard strain A. muciniphila ATCC BAA-835 has been shown to help reduce obesity, significant functional variations among different strains remain a concern. To address this issue, our research investigated the impact of A. muciniphila Akk11 (Akk11), a strain sourced from the feces of healthy infants, in both its live and pasteurized forms on obesity.MethodsMale C57BL/6J mice were fed a high-fat diet to induce obesity and then treated with either live or pasteurized A. muciniphila Akk11. Body weight, adiposity, intestinal histology, gut microbiota composition (via 16S rRNA gene sequencing), and short-chain fatty acids (SCFAs) levels were assessed after the intervention period.ResultsWe observed that both forms of Akk11 provided protective benefits in obese mice, as evidenced by reductions in Lee’s index and the area of white adipose tissue. In terms of intestinal health, both live and pasteurized Akk11 notably increased the number of goblet cells in the colon while also significantly improving mucosal integrity and enhancing the expression of tight junction proteins. Notably, 16S rRNA gene sequencing revealed that pasteurized Akk11 altered the gut microbiota composition, with significant differences in the dominant intestinal microbiota. The pasteurized Akk11 group showed a marked increase in the abundance of the Akkermansia genus. Additionally, both treatments influenced the levels of short chain fatty acids, though their effects varied. Compared to the control group, both live and pasteurized Akk11 treatments led to higher levels of isobutyric and valeric acids. Furthermore, the live Akk11 significantly boosted propionic acid levels, while the pasteurized Akk11 significantly increased butyric acid levels.DiscussionThese findings indicated that both live and pasteurized Akk11 could serve as promising strategies for alleviating obesity linked to high-fat diets. This research supports the potential use of various A. muciniphila preparations as therapeutic options for obesity and related health issues in humans.